Why Sustainability Principles should integrate Global Justice Concerns. Issue 3 (2nd September 2017) - Zwarthoed, Danielle
Abstract: Curren and Metzger develop a normative account of sustainability without prejudging the relationships between sustainability and global justice. This commentary propounds an alternative methodology whereby sustainability principles are determined in conjunction with principles of global justice. I suggest this methodology is better equipped to address two issues Living well raises. First, the authors' sufficiency view involves an inescapable tension between permitting a generation to consume more than the threshold of opportunities to live well and securing an equivalent threshold for other generations. Addressing this tension requires an account of how much is owed to the current generation. Second, their third principle of sustainability ethics establishes a duty to 'seek fair terms of cooperation conducive to sustainability'. Fleshing out this principle requires an account of the fair distribution of the burdens of transitioning to a sustainable world and of the extent to which the existing distribution of goods falls short of justice.